2019
DOI: 10.5897/jdae2018.1038
|View full text |Cite
|
Sign up to set email alerts
|

Value chain analysis of fruits: The case of mango and avocado producing smallholder farmers in Gurage Zone, Ethiopia

Abstract: The study was aimed to analyze avocado and mango value chains actors and identify factors that determine avocado and mango market supply in the selected area of Gurage zone. A total of 259 avocado and mango producers were selected through three-stage sampling technique and 151 traders from different level were used to collect primary data using questionnaire and semi-structured interview. Descriptive and econometrics method of analysis were applied for analysis. Value chain approach analysis result revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
0
3
1
Order By: Relevance
“…This result is different from those of Mengesha et al (2018) in Ethiopia, where they found that the wholesalers received the highest marketing margin (34.62%) and highest profit share (36.75%), while the producers received the least marketing margins (15.17%) from avocado and mango trade.…”
Section: Analysis Of the Financial Profitability Of Value Chainscontrasting
confidence: 88%
See 1 more Smart Citation
“…This result is different from those of Mengesha et al (2018) in Ethiopia, where they found that the wholesalers received the highest marketing margin (34.62%) and highest profit share (36.75%), while the producers received the least marketing margins (15.17%) from avocado and mango trade.…”
Section: Analysis Of the Financial Profitability Of Value Chainscontrasting
confidence: 88%
“…Baviera-Puig et al (2017) in their study of the Rabbit meat sector value chain in Spain identified four components in the rabbit meat chain: producers, input suppliers, abattoirs and cutting plants and distribution. Mengesha et al (2018) in their study of Value chain analysis of fruits in Ethiopia found that mango and avocado producer, input suppliers, collectors, retailers, wholesalers and consumers were the main actors in mango and avocado value chain.…”
Section: Mapping Of Rabbit Value Chainsmentioning
confidence: 99%
“…The findings of this paper are consistent with Thebethe (2013) who found that age, level of education, marital status, land size, off-farm income and experience are significant determinants of allocative efficiency in sugarcane farming among Mpumalanga growers, in South Africa. Similarly, Mengesha et al (2019) found that the sex of the household, land allocated to mango, and farming experience were significant factors determining mango market supply in the mango value chain in Ethiopia. A goodness-of-fit for the model computed for this dataset comprises the R-Square and F-statistic.…”
Section: Determinants Of Sugarcane Production (Yeild-t/ha)mentioning
confidence: 94%
“…Consequently, it has been widely used by many recent studies [52][53][54] in determining the sample size for their studies. Finally, the sample size was distributed using the probability proportional to the sample size.…”
Section: Sampling Techniquesmentioning
confidence: 99%
“…On the other hand, if the distance to the high value market increases, the transportation cost will also increase and the farmers obligated to sell their avocado to traditional village market. The studies by Girmalem et al, (2019); Mengesha et al, (2019) found that the distance to the market has the negative in uence on the farmer's participation in market. Therefore, it was hypothesized that the modern market is far from the farm the farmer more selling to traditional market chain and then the income of farmer become low.…”
Section: Distance To the High-value Marketmentioning
confidence: 99%